2004
DOI: 10.1097/00005721-200405000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Deep Vein Thrombosis in Pregnancy

Abstract: This article provides a review of the incidence, pathophysiology, and treatment of deep vein thrombosis (DVT) in pregnancy, a rare but serious complication of pregnancy. The incidence of DVT in pregnancy varies widely, but it is a leading cause of maternal morbidity in both the United States and the United Kingdom. Risk factors during pregnancy include prolonged bed rest or immobility, pelvic or leg trauma, and obesity. Additional risk factors are preeclampsia, Cesarean section, instrument-assisted delivery, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…This may have additional health benefits including less postoperative immobility, which is a well-known risk factor for thromboembolic disease. 14 There has certainly been a drive in the UK to change the traditional practice of inpatient care to more day case surgery and outpatient care. This has been driven by patient's choice and economic considerations.…”
Section: Discussionmentioning
confidence: 99%
“…This may have additional health benefits including less postoperative immobility, which is a well-known risk factor for thromboembolic disease. 14 There has certainly been a drive in the UK to change the traditional practice of inpatient care to more day case surgery and outpatient care. This has been driven by patient's choice and economic considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Bed rest or immobility, pelvic or leg trauma have previously been reported to be risk factors for DVT. 2 Although epidemiologic studies have demonstrated many risks a defi cit of blood group O among patients with DVT, few studies have evaluated the importance of blood group in these high-risk patients. Recently non-O blood type was independently associated with risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…Cesarean section is a known risk factor for DVT. 2 However, one of the studies failed to observe the risk of DVT among pregnant women undergoing cesarean section. 10 Smoking is not unusual among Sudanese women, hence it was not investigated in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover other markers reflecting hypercoagulability (such as D-dimer and/or prothrombin fragment) are increased during pregnancy. 5,6 Different polymorphisms of thrombophilic disorders are diagnosed in up to 40% of women who have experienced recurrent miscarriages. However, this association depends on the type of thrombophilic disorder and the gestational age at which fetal loss occurs.…”
Section: Introductionmentioning
confidence: 99%